Efisiensi Kapasitas Lentur Beton Pracetak (U-Ditch) Dengan Model Dinding Corrugated - Erwin Syaiful Wagola; Muhammad Tharik Kemal (Rekayasa Sipil, 2020)
This study discusses to analyze the flexural capacity and efficiency of the corrugated U-Ditch type with dimensions of 50x50 cm to the normal U-Ditch type. In this research using JIS (Japan International Standard) method for The U-Ditch Corrugated test. The results showed that the flexural behavior of the Normal Type U-Ditch is linear to collapse with a crack pattern occurring on the U-Ditch wall.  The bending of the U-Ditch Corrugated type tends to be linear until it collapses with a crack pattern occurring in the structural wall. The magnitude of the bending moment capacity for the normal type is 9.11 kN.m and capacity of the U-Ditch corrugated type is 8.05 kN. m where the efficiency of bending capacity is 98%.